2017
DOI: 10.4155/fsoa-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances in Kinase Enzymes and Inhibitors for Cardiovascular Disease Treatment

Abstract: The targeting of protein kinases has great future potential for the design of new drugs against cardiovascular diseases (CVDs). Enormous efforts have been made toward achieving this aim. Unfortunately, kinase inhibitors designed to treat CVDs have suffered from numerous limitations such as poor selectivity, bad permeability and toxicity. So, where are we now in terms of discovering effective kinase targeting drugs to treat CVDs? Various drug design techniques have been approached for this purpose since the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Different isoenzymes of PKC may play different roles in angiogenesis in diverse stem cell types under various conditions. Future studies are indicated to clarify the potential impacts of PKC isoenzymes in cardiovascular disease [30].…”
Section: Discussionmentioning
confidence: 99%
“…Different isoenzymes of PKC may play different roles in angiogenesis in diverse stem cell types under various conditions. Future studies are indicated to clarify the potential impacts of PKC isoenzymes in cardiovascular disease [30].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are the predominant cellular source of ROS and energy production. If mitochondria become damaged, their oxidative phosphory-lation capacity is reduced, which can subsequently result in excessive ROS production and abnormal calcium homeostasis, thereby promoting cardiomyocyte necroptosis [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…There are a myriad of kinases and phosphatases regulated by cytosolic Ca 2+ signals, which are sensitive to Ca 2+ location, size, and frequency 14. One such Ca 2+ sensor, Ca 2+ /calmodulin-dependent enzyme (CAMK), controls cardiomyocyte growth, differentiation, and development, which are also important factors in the pathophysiology of various cardiac diseases 15, 16. The other, calcineurin, has recently been demonstrated to have beneficial effects on myocardial hypertrophy and ventricular function 17.…”
Section: Pgc-1 Signaling Networkmentioning
confidence: 99%